Efficient Separation of Photogenerated Charges in Sandwiched Bi2S3−BiOCl Nanoarrays/BiVO4 Nanosheets Composites for Enhanced Photocatalytic Activity. Issue 12 (29th April 2020) - Li, Huali; Chen, Yajie; Li, Li; Liu, He; Jiang, Haiyu; Du, Lizhi; Tian, Guohui
Abstract: The development of cost‐efficient and feasible strategies for producing efficient photocatalysts is crucial to advance photocatalytic pollutants degradation. Herein, we report a high photocatalytic active hierarchical sandwiched Bi2 S3 −BiOCl nanoarrays/BiVO4 nanosheets composites fabricated using biomass‐derived BiVO4 porous nanosheets as starting substrate material. BiVO4 porous nanosheets were first prepared via an impregnation‐calcination process using biomass template method. Subsequently, the ion exchange reactions during solvothermal reaction realized the in situ nucleation and growth of Bi2 S3 nanorods and BiOCl nanoflakes nanoarrays from both sides of BiVO4 porous nanosheets, resulting in the formation of hierarchical sandwiched Bi2 S3 −BiOCl nanoarrays/BiVO4 nanosheets composites. Specifically, well‐defined Bi2 S3 nanorods and BiOCl nanoflakes nanoarrays are vertically grown on the surface of BiVO4 nanosheets to provide plenty of accessible active sites and enable visible light harvesting. The tight contact between different components promises fast electron transfer and excellent durability. Consequently, optimized sandwiched Bi2 S3 −BiOCl/BiVO4 composite exhibits superior photocatalytic activity for pollutants degradation. Abstract : Photocatalysis : The sandwiched Bi2 S3 −BiOCl/BiVO4 composites were fabricated and exhibited better photocatalytic performance than single BiVO4 and binary Bi2 S3 /BiVO4 composites due to the accelerated photogenerated charge transfer and separation, abundant exposed active sites, and enhanced visible light absorption.